Trombocitopenia primária imune com púrpura palpável: um relato de caso. - Marcela Bezerra Marques; Alexia Lavínia Holanda Gama; Hellen Stephane Pita Dantas; Filipe Marinho Pinheiro da Câmara; Tereza Rebecca de Melo e Lima; Maryana Dayhara Costa Erlich (Sociedade Brasileira de Pediatria, 2024)
Immune thrombocytopenia is a relatively common bleeding disorder characterized by isolated destruction of platelets by autoantibodies, with a typically acute onset, benign course and self-limiting in most cases. The aim of this report is to present a rare case of Primary Immune Thrombocytopenia (ITP) with palpable purpura, an uncommon manifestation in this disease and little described in the literature. This is a 12-year-old female adolescent who presented with palpable purpura, ecchymosis and oral cavity bleeding associated with thrombocytopenia and anemia. Initial investigation excluded autoimmune diseases, vasculitis, lymphoproliferative diseases and coagulation disorders, in addition to the myelogram showing typical findings of ITP: hypercellular bone marrow with megakaryocytic hyperplasia and decreased thrombocytogenesis. Due to the diversity of clinical presentation and the possibility of atypical manifestations, the diagnosis is often challenging, as in the case of this patient in which the main finding on physical examination was the presence of palpable purpura.